PENGARUH LABA AKUNTANSI DAN ARUS KAS OPERASI TERHADAP RETURN SAHAM PADA PERUSAHAAN MANUFAKTUR YANG TERDAPAT DI BURSA EFEK INDONESIA (BEI) - , KENSO DWI ATMOJO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Cash flow information derived from operating activities Cash flow statement of the company, describes a company's ability to generate cash, so that information about cash flow operating activities deemed to affect users of financial information in making decisions related to that information. With samples taken from the Indonesia Stock Exchange (BEI), this study aim to analyze whether cash flow operating activities can positively affect stock returns to be obtained and whether the accounting profit may also positively affect stock returns to be obtained. Independent variable in this study is comprised of two accounting earnings and operating cash flow. As for the dependent variable is the return on the stock. The sample in this study there are 33 manufacturing company listed on Indonesia Stock Exchange (IDX). Sample was determined by purposive sampling technique in order to obtain a representative sample in accordance with the specified criteria. The results of this study showed that accounting earnings and operating cash flow positively affect on stock returns, which means higher accounting earnings and operating cash flow will runs balanced with the greater benefits obtained for the shareholders.